2000
DOI: 10.1046/j.1365-2036.2000.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of unfractionated heparin with corticosteroids in severe active inflammatory bowel disease

Abstract: Background: Heparin therapy may be effective in steroid resistant inflammatory bowel disease. Aim: A randomized pilot study, to compare unfractionated heparin as a first‐line therapy with corticosteroids in colonic inflammatory bowel disease. Methods: Twenty patients with severe inflammatory bowel disease (ulcerative colitis, n=17; Crohn’s colitis, n=3) were randomized to either intravenous heparin for 5 days, followed by subcutaneous heparin for 5 weeks (n=8), or high‐dose intravenous hydrocortisone for 5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 30 publications
(43 reference statements)
1
50
0
5
Order By: Relevance
“…In one study of patients with UC, all of whom had rectal bleeding, three of the 12 patients receiving full anticoagulation with heparin developed increased rectal bleeding, one requiring an urgent operation [20] . In the other study, of eight patients with IBD who received a continuous infusion of unfractionated heparin, no major bleeding events occurred [21] . Other trials have examined treatment with low molecular weight heparin.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of patients with UC, all of whom had rectal bleeding, three of the 12 patients receiving full anticoagulation with heparin developed increased rectal bleeding, one requiring an urgent operation [20] . In the other study, of eight patients with IBD who received a continuous infusion of unfractionated heparin, no major bleeding events occurred [21] . Other trials have examined treatment with low molecular weight heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Evans et al found that heparin was effective in treating corticosteroid-resistant ulcerative colitis [120] , and Yoshikane et al reported that heparin was very effective in the treatment of disseminated intravascular coagulation (DIC) caused by ulcerative colitis [121] . Recently, heparin was even suggested as a first line therapy in the treatment of severe colonic inflammatory bowel disease [122] , but should be administered in hospitalized patients only because of the risk of possible serious bleeding [123] . To overcome bleeding side effect, low molecular weight heparin (LMWH) was employed as adjuvant therapy [124] , and the patients showed good clinical and laboratory response with no severe adverse effects [125,126] .…”
Section: Involvement Of Heparin In Pathogenesis Of Ibdmentioning
confidence: 99%
“…Three randomized, blinded studies published as abstracts only were excluded after attempts to contact the authors for further details about methodology and results were not successful. [22][23][24] Ang et al 25 enrolled patients with UC and Crohn's disease. This study was excluded because separate results were not provided for patients with UC.…”
Section: Description Of Studiesmentioning
confidence: 99%